Thyroid Function Abnormalities and Outcomes in Hospitalized Patients with COVID-19 Infection: A Cross-Sectional Study - Patel, Deepika; Naik, Dukhabandhu; Kamalanathan, Sadishkumar; Tamilarasu, Kadhiravan; Sahoo, Jayaprakash; Roy, Ayan; Merugu, Chandhana; Suryadevara, Varun (Hormone and Metabolic Research, 2023)
Thyroid gland can be affected by the COVID-19 infection. The pattern of thyroid function abnormality reported in COVID-19 is variable; in addition, some drugs used in COVID-19 patients like glucocorticoids and heparin can affect the thyroid function tests (TFT). We conducted an observational, cross-sectional study of thyroid function abnormalities with thyroid autoimmune profile in COVID-19 patients with varying severity from November 2020 to June 2021. Serum FT4, FT3, TSH, anti-TPO, and anti-Tg antibodies were measured before the initiation of treatment with steroids and anti-coagulants. A total of 271 COVID-19 patients were included in the study, of which 27 were asymptomatic and remaining 158, 39, and 47 were classified to mild, moderate and severe categories, respectively, according to MoHFW, India criteria. Their mean age was 49±17 years and 64.9% were males. Abnormal TFT was present in 37.2% (101/271) patients. Low FT3, low FT4, and low TSH were present in 21.03%, 15.9% and 4.5% of patients, respectively. Pattern corresponding to sick euthyroid syndrome was the most common. Both mean FT3 and FT3/FT4 ratio decreased with increasing severity of COVID-19 illness (p=0.001). In multivariate analysis, low FT3 was associated with increased risk of mortality (OR 12.36, 95% CI: 1.23–124.19; p=0.033). Thyroid autoantibodies were positive in 58 (27.14%) patients; but it was not associated with any thyroid dysfunction. Thyroid function abnormality is common among COVID-19 patients. Both low FT3 and FT3/FT4 ratio are indicators of disease severity while low FT3 is a prognostic marker of COVID-19 associated mortality.
Keywords: SARS-CoV2; low FT3 syndrome; mortality; sick euthyroid syndrome; thyroiditis